Analisa Penggunaan Alat Kontrasepsi Hormonal Terhadap Tekanan Darah - Eva Santi Hutasoit; Yessi Azwar (HEALTH CARE : JURNAL KESEHATAN, 2019)
Hypertension is a condition when blood pressure in blood vessels increases chronically (Suiraoka, 2012). The risk of increasing this blood pressure is related to race, family history of hypertension, obesity, diet / food intake, smoking and the length of time the combination hormonal contraceptive is used. Family acceptors who use hormonal contraception over a period of time often complain of health problems, one of the health problems that are often experienced by hormonal contraceptive acceptors is hypertension or high blood pressure. Hormonal contraception can cause high blood pressure (hypertension) in approximately 4-5% of women who have normal blood pressure before taking the drug, and can increase blood pressure in 9-16% of women who have suffered hypertension before. The type of research used in this study is quantitative, with analytic research design and with a cross sectional approach, namely research conducted simultaneously. The number of samples is 54 mothers who are KB KBtor. From the results of the study, it was found that respondents who used hormonal contraception experienced an increase in blood pressure by 37 people (84.1%), while those who did not experience a rise in blood pressure were 7 people (15.9%). Respondents who did not use hormonal contraception experienced an increase in blood pressure by 5 people (50.0%), while those who did not experience an increase in blood pressure were 5 people (50.0%). From the Chi-square test results obtained a value of 0,045 (Pvalue 0,045 <α 0,05) and OR 5,286. This shows that Ha is accepted which means that there is a relationship between the use of hormonal contraception and an increase in blood pressure. OR = 5,286 showed that the use of hormonal contraception 5 times was associated with increased blood pressure.